2011
DOI: 10.1177/0013164411408074
|View full text |Cite
|
Sign up to set email alerts
|

Multigroup Generalizability Analysis of Verbal, Quantitative, and Nonverbal Ability Tests for Culturally and Linguistically Diverse Students

Abstract: For educators seeking to differentiate instruction, cognitive ability tests sampling multiple content domains, including verbal, quantitative, and nonverbal reasoning, provide superior information about student strengths and weaknesses compared with unidimensional reasoning measures. However, these ability tests have not been fully evaluated with respect to fairness and validity for English-language learners (ELL). In particular, reliability is an important aspect of validity that has not been sufficiently eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Another study found that the reliability of the verbal battery was adequate (Φ = .82) for ELL students, although lower than that of non‐ELL students (Φ = .96). See Lakin and Lai (2012) for a detailed exploration of the reliability of the CogAT for ELL students.…”
Section: Methodsmentioning
confidence: 99%
“…Another study found that the reliability of the verbal battery was adequate (Φ = .82) for ELL students, although lower than that of non‐ELL students (Φ = .96). See Lakin and Lai (2012) for a detailed exploration of the reliability of the CogAT for ELL students.…”
Section: Methodsmentioning
confidence: 99%
“…The scores were much more consistent, however, in grades 5-9 (Naglieri & Ronning, 2000). Lakin and Lai (2012) tell us that multi-dimensional tests that include linguistic and mathematical reasoning are better at predicting academic achievement because nonverbal tests do not specifically test language or mathematical skills. These same multidimensional tests, though, also show greater discrepancies between English language learners and native English speakers.…”
Section: Background Of the Studymentioning
confidence: 94%
“…Nonverbal tests are already utilized in numerous schools to identify students for gifted programs (Giessman, Gambrell, & Stebbins, 2013). Nonverbal tests, however, have not been fully evaluated to determine fairness in their use for admissions (Lakin & Lai, 2012). A nonverbal test should be identified and studied for use in private schools as part of the admissions process for secondary students in order to help predict academic achievement, while at the same time reducing recognized biases in the testing process.…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have linked the disproportionate number of ELL students referred to special education to cultural bias in the evaluation procedures used to identify students with disabilities (Lakin & Lai, 2012). Macswan and Rolstad (2006) found that the test measurements used may not accurately reflect an ELL student's ability.…”
Section: Factors and Practices Associated With Disproportionalitymentioning
confidence: 99%